(untitled) - FEBRIAHATI, ATIKA (RETAIN : Journal of Research in English Language Teaching, 2013)
Penggunaan kata derivatif sangat penting karena makna kata bergantung pada kesesuaiannya. Pada realitanya, penguasaan kata derivatif masih belum bisa dicapai secara maksimal pada level perguruan tinggi, sehingga mahasiswa masih membuat beberapa kesalahan dalam karangannya. Pada dasarnya, konsep kata derivatif dalam bahasa Inggris berbeda dengan bahasa Indonesia. Hal ini menyebabkan mahasiswa Indonesia menemui kesulitan untuk menguasai kata derivatif, termasuk mahasiswa jurusan Bahasa Inggris. Berdasarkan masalah tersebut, studi ini dirancang untuk mendeskripsikan bagaimana mahasiswa jurusan Bahasa Inggris di UNESA menggunakan kata derivatif dalam karangannya. Studi ini termasuk dalam studi deskriptif kualitatif dan penelitian dokumenter dengan menggunakan karangan mahasiswa dalam post-test program IC. Instrumen penelitian yang digunakan dalam studi ini adalah post-test dan ceklist. Ada tiga langkah dalam menganalisis data, mengidentifikasi kesalahan, mengklasifikasi kesalahan, dan mengidentifikasi penyebab kesalahan. Setelah melelui tahap analisis berdasarkan surface strategy taxonomy, hasil menunjukkan bahwa mahasiswa menemui kesulitan dalam menyusun kata derivatif. Abstract Derivative words usage is imperative since the meaning of words depend on its conformity. The reality in Indonesian college brings a phenomenon where the goal of acquiring derivative words itself does not come true so that the students produce errors in their composition. Basically, the concept of derivative words in English is different from that of Bahasa Indonesia. That is why it is difficult for Indonesian students, including university students of English major, to acquire derivative words. Dealing with the problem, this study was designed to describe the students of English Department in UNESA use derivative words in their composition. By employing the concept of descriptive qualitative study and documentary research, this study used the students’ composition produced in the writing test after they finished the IC Program. The instruments of this study were post-test short essay and check list. There were three steps in analyzing the data, identification of errors, classification of errors, and identifications of the cause of errors. Having analyzed the errors based on the surface strategy taxonomy, the results showed that the students found difficulties on constructing derivative words.